NUMERICAL SIMULATION OF MAXWELL EQUATION USING FINITE DIFFERENCE METHOD IN CASE OF SUBSURFACE CONDUCTIVITY PARAMETER - Adam Sukma Putra; Sismanto Sismanto (Universitas Tanjungpura, 2022)
The aim of this project is to solve the Maxwell’s Equation using the finite difference (FD) method. We test the governing equation by discretizing the equation in 1-Dimensional System to describe the distribution of the magnitude of Electric and Magnetic Field within the subsurface layer. We assume that earth layer has constant conductivity (σ) where σ>>εω as a consequence that the system is homogenous and isotropic. We consider that the distribution of the field is described by the diffusion equation. We apply the modified form of FD method with Crank-Nicholson to improve the precision of the simulation.